Financing Singapore's small and medium-sized enterprises in China. - Blake W. Bratt. (2008)
This case descriptively explores the experiences and challenges encountered by Wangi Industrial Company Private Limited when it first ventured in to Shanghai. It examines the difficulties and constraints faced by the Company when seeking financing for its investment in China. A detailed analysis of China’ banking industry and the major financing obstacles facing Singapore’s SMEs in China is provided.